2011
DOI: 10.1111/j.1755-6686.2011.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic and Anti‐phospholipid Syndromes: Multisystem Conditions Associated With Acute Myocardial Infarction in Young Patients

Abstract: Acute myocardial infarction is relatively uncommon in patients under the age of 40 years. Unlike the older patients where rupture of coronary artery atherosclerotic plaque is the main underlying pathology, the pathogenesis in younger patients can be varied and may require different diagnostic and therapeutic approaches. Hypercoagulable state associated with nephrotic syndrome and antiphospholipid syndrome can lead to the development of occlusive coronary artery thrombus in absence of atherosclerotic coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This phenomenon is twice as common in women than in men and is associated with the perinatal period [9,14]. A hypercoagulable state is estimated to be responsible for 5% of MI cases in young patients and, similarly to congenital coronary artery anomalies, may be the first manifestation of the underlying abnormality [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is twice as common in women than in men and is associated with the perinatal period [9,14]. A hypercoagulable state is estimated to be responsible for 5% of MI cases in young patients and, similarly to congenital coronary artery anomalies, may be the first manifestation of the underlying abnormality [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…The hypercoagulability associated with NS can result in the development of an occlusive coronary artery thrombus in absence of atherosclerotic coronary artery disease [49]. ACS, ST-elevation myocardial infarction and non-ST-elevation myocardial infarction is not a very rare complication; sometimes, it can be the first manifestation in primary MN [4952]. the accurate diagnosis of the complication is imperative for suitable management and secondary prevention in primary MN [53].…”
Section: Results: Prevention Of Thrombogenesis and The Anticoagulant mentioning
confidence: 99%
“…We analyzed the existing case reports and reviews that detailed the treatment process and found that, in general, in primary MN patients with a confirmed diagnosis of ACS, the treatment regimen of ACS was almost similar to that of the general population with ACS. It was noteworthy that a majority of primary MN patients with ACS continued the previous primary MN treatment protocol during the entire treatment period until they obtained remission (partial or complete remission) and the protocol was completed [4952]. Provided that there is an additional strong indication that requires anticoagulant therapy, over and above that of their primary MN with ACS, the patient might have extra lifelong anticoagulation therapy [49].…”
Section: Results: Prevention Of Thrombogenesis and The Anticoagulant mentioning
confidence: 99%
See 1 more Smart Citation